2009
DOI: 10.1002/hep.23113
|View full text |Cite
|
Sign up to set email alerts
|

The myth of occult hepatitis C infection #

Abstract: We read with interest the review by Welker and Zeuzem on occult hepatitis C virus (HCV) infection and also the reply by Carreno et al. 1,2 The latter reported in their answer to Welker and Zeuzem that HCV can replicate in patients with occult HCV infection. Because this conclusion would have substantial consequences for patients considered cured of their HCV infection, as well as for the health care system, the data must be interpreted most carefully. They reported two studies that "unconvincingly failed to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…The possibility of occult infection causing symptoms in our clearedv HCV sample also appears highly improbable given their consistent PCR ‘negative’ status over 20 years of annual surveillance. This is further supported by recent publications purporting to debunk the ‘myth’ of occult HCV infection . This investigation, which to the author's knowledge is the first to examine both chronically infected and cleared HCV individuals with an iatrogenic exposure history as a single sample, found relatively equal representation of CHC and cleared HCV individuals in both impaired and nonimpaired HRQoL subgroups.…”
Section: Discussionsupporting
confidence: 71%
“…The possibility of occult infection causing symptoms in our clearedv HCV sample also appears highly improbable given their consistent PCR ‘negative’ status over 20 years of annual surveillance. This is further supported by recent publications purporting to debunk the ‘myth’ of occult HCV infection . This investigation, which to the author's knowledge is the first to examine both chronically infected and cleared HCV individuals with an iatrogenic exposure history as a single sample, found relatively equal representation of CHC and cleared HCV individuals in both impaired and nonimpaired HRQoL subgroups.…”
Section: Discussionsupporting
confidence: 71%
“…Barril and colleagues found an OCI prevalence of 45% in 109 haemodialysis patients [13], and the same group of investigators claimed there was a potential transmission risk of OCI [14], as they found a high OCI prevalence among relatives of OCI patients, comparable to that found among family members of patients with chronic HCV infection. Conversely, other authors did not find OCI in immune-suppressed subjects [15][16], in 28 onco-haematological [17] patients, or in 26 kidney-transplant patients [18].…”
Section: Introductionmentioning
confidence: 89%
“…Specifically, they found that the presence of OCI among the relatives of individuals they studied was comparable to that found among family members of patients with overt HCV infection. The Barril et al report [ 60 ] and others [ 64 , 65 ] however stand in contrast to that of other authors [ 39 , 66 ] who were not able to identify cases of OCI in different cohorts of immune-suppressed subjects consisting of 28 oncohematological patients [ 67 ] and 26 kidney-transplant recipients [ 68 ].…”
Section: Oci In Immune Impaired Individualsmentioning
confidence: 98%